Wavelet-Galerkin Quasilinearization Method for Nonlinear Boundary Value Problems - Umer Saeed; Mujeeb ur Rehman (Abstract and Applied Analysis)
A numerical method is proposed by wavelet-Galerkin and quasilinearization approach for nonlinear boundary value problems. Quasilinearization technique is applied to linearize the nonlinear differential equation and then wavelet-Galerkin method is implemented to linearized differential equations. In each iteration of quasilinearization technique, solution is updated by wavelet-Galerkin method. In order to demonstrate the applicability of proposed method, we consider the various nonlinear boundary value problems.